ARL4C might serve as a prognostic factor and a novel therapeutic target for gastric cancer: bioinformatics analyses and biological experiments. Issue 8 (16th March 2021) - Xie, Ning; Bai, Yunfan; Qiao, Lu; Bai, Yuru; Wu, Jian; Li, Yan; Jiang, Mingzuo; Xu, Bing; Ni, Zhen; Yuan, Ting; Shi, Yongquan; Wu, Kaichun; et al.
Abstract: The ADP‐ribosylation factor‐like proteins (ARLs) have been proved to regulate the malignant phenotypes of several cancers. However, the exact role of ARLs in gastric cancer (GC) remains elusive. In this study, we systematically investigate the expression status, interactive relations, potential pathways, genetic variations and clinical values of ARLs in GC. We find that ARLs are significantly dysregulated in GC and involved in various cancer‐related pathways. Subsequently, machine learning models identify ARL4C as one of the two most significant clinical indicators among ARLs for GC. Furthermore, ARL4C silencing remarkably inhibits the growth and metastasis of GC cells both i n vitro and in vivo. Moreover, enrichment analysis indicates that ARL4C is highly correlated with TGF‐β1 signalling. Correspondingly, TGF‐β1 treatment dramatically increases ARL4C expression and ARL4C knockdown inhibits the phosphorylation level of Smads, downstream factors of TGF‐β1. Meanwhile, the coexpression of ARL4C and TGF‐β1 worsens the prognosis of GC patients. Our work comprehensively demonstrates the crucial role of ARLs in the carcinogenesis of GC and the specific mechanisms underlying the GC‐promoting effects of TGF‐β1. More importantly, we uncover the great promise of ARL4C‐targeted therapy in improving the efficacy of TGF‐β1 inhibitors for GC patients.